Clinical features of patients diagnosed with recidivan cutaneous leishmaniasis (Annals of Medical Research, 2021)
Aim: Cutaneous leishmaniasis (CL) is a disease with chronic nodulo-ulcerative lesions on the skin that heals with atrophic scars. This study aims to investigate the clinical features of patients admitted to our clinic and diagnosed as recidivan CL.Material and Methods: This retrospective study included 11 patients who were admitted to our skin and venereal diseases clinic between October 2017 and July 2019 and who were diagnosed as recidivan CL by anamnesis, clinical and microscopic examination. Clinical characteristics of the patients such as age, sex, survival in the endemic region, intralesional or systemic antimony therapy and number, location, size and duration of the lesions were recorded.Results: Seven (63.6%) of the 11 patients were male and 4 (36.4%) were female. The mean age of the patients was 13.8 ± 4.04 years. All of the patients in the study had one lesion on their face. The mean lesion duration was 36.27 ± 24.3 months. The mean lesion size was 6.9 ± 3.4 cm. Before the diagnosis, 2 (18.2%) patients received intralesional antimony treatment, 1 patient (9.1%) received systemic antimony treatment, and 8 (72.7%) patients did not receive any treatment.Conclusion: In conclusion, recidivan CL is a rare form of chronic CL. Because parasites are rare in the lesions, the diagnosis is usually delayed and therefore the lesions can cause destruction and deformity. Prospective studies with a large number of patients are needed to better understand the clinical findings of recidivan CL.
Keywords: Chronic cutaneous leishmaniasis; recidivan